Analysis of pH and release of calcium of association between melaleuca alternifolia oil and calcium hydroxide - Maiara GIONGO; Rogério Aparecido Minini dos SANTOS; Sandra Mara MACIEL; Marina de Lourdes Calvo FRACASSO; Fausto Rodrigo VICTORINO (Universidade Estadual Paulista, 2017)
Abstract Introduction The use of intracanal medications with antimicrobial properties is essential for decontaminating root canals during endodontic treatment. Calcium hydroxide is used for this because of its excellent properties. Melaleuca alternifolia oil has shown medicinal importance by demonstrating antifungal and bactericidal action against proven human pathogens. Objective To evaluate the physical and chemical aspects such as pH and calcium release, of Melaleuca alternifolia oil associated with calcium hydroxide, during different time intervals. Material and method Calcium hydroxide powder was added to vehicles to reach a concentration of 72mg / 0.1mL. Three groups were formed: Group I: Calcium Hydroxide + Distilled Water; Group II: Calcium hydroxide + Propylene Glycol; Group III: Calcium hydroxide + Melaleuca oil. The pH of each group was measured after time intervals of 10 minutes; 24 and 48 hours; 7, 15 and 30 days after tooling by a pH meter. Calcium release was analyzed by atomic absorption spectrometry equipped with a calcium hollow cathode lamp. Data were statistically analyzed by using the Kruskall-Wallis and Dunn test. Result Group II showed high pH, similar to group III that remained uniform at 15 and 30 days. Calcium release that began after 24 hours, was similar in Groups II and III, and showed a peak release in 48 hours. Conclusion The association of Melaleuca oil with calcium hydroxide showed good results in the pH and calcium release analyses, and showed action similar to that of propylene glycol + calcium hydroxide.